Training of social education on prevention of the victim behavior - Meiramkul Murzagulova; Kalipa Atemova; Aliya Kudaibergenova; Elmira Bayarystanova; Ardak Sembayeva; Aiym Massimbayeva; Ltifat Zhanybekova (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study focused on assessing the impact of a specialized training program in dealing with victim behavior among teenagers. A total of 200 social educators from Kazakhstan participated in the study, evenly divided into an experimental group, which underwent training, and a control group, which did not receive training. A 100-point test was used in the study to evaluate pre-and post-training assessments. The average score on the pre-tests in both groups was 43. After the training, a significant increase in scores was observed in the experimental group, averaging 75.74, indicating the effectiveness of the training. The control group showed a slight increase with an average post-test score of 48.73. Statistical analysis underscored the impact of the training. Paired sample t-test for the experimental group revealed a significant mean difference with a significant value (p<0.001). The change in the control group was also significant but small (p<0.001). Independent samples t-test between the group results after testing indicated that the success of the experimental group was significantly higher (p<0.001). These results demonstrate the value of targeted training to enhance the capabilities of social educators in managing the behavior of victimized adolescents, emphasizing the need for such specialized programs in educational institutions.